The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.3109/01677068909066203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the Ocellar Visual System in Normal and MutantDrosophila Melanogaster

Abstract: Between the two compound eyes on the vertex on the adult head are the three simple eyes, ocelli. Transmission and scanning electron microscopy were used to investigate the corneal lenses, ocellar photoreceptors, and axonal projections in normal and mutant Drosophila melanogaster. In wild type flies, the cornea consists of about 45 lamellae. It has corneal nipples distally and is underlaid with a monolayer of corneagenous cells. Retinula cells have open rhabdomeres of about 2 microns (diameter) x 7 microns (len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Cell identities in the developing eye of Drosophila are determined by induction, and mutations in several genes that encode putative transcription factors have been shown to disrupt normal eye development (for reviews, see Tomlinson 1988;Banerjee and Zipursky 1990). Here, we show that one of these genes, glass, encodes a site-spe1present address: Molecular Biology Section, Department of Biological Sciences, University of Southern California, University Park, Los Angeles, California 90089 USA.cific DNA-binding protein and that glass function, in its broadest sense, is regulated at the protein level.The glass gene is required for the normal development of photoreceptor cells in all three organs in which they occur: the adult compound eye (Johannsen 1924;Garen and Kankel 1983), the adult simple eyes or ocelli (Stark et al 1984;Moses et al 1989;Stark and Sapp 1989), and the larval photoreceptor or Bolwig's organ (Moses et al 1989). In the retina, we demonstrated that only the photoreceptor cells have a cell-autonomous requirement for glass function (Moses et al 1989).…”
mentioning
confidence: 58%
“…Cell identities in the developing eye of Drosophila are determined by induction, and mutations in several genes that encode putative transcription factors have been shown to disrupt normal eye development (for reviews, see Tomlinson 1988;Banerjee and Zipursky 1990). Here, we show that one of these genes, glass, encodes a site-spe1present address: Molecular Biology Section, Department of Biological Sciences, University of Southern California, University Park, Los Angeles, California 90089 USA.cific DNA-binding protein and that glass function, in its broadest sense, is regulated at the protein level.The glass gene is required for the normal development of photoreceptor cells in all three organs in which they occur: the adult compound eye (Johannsen 1924;Garen and Kankel 1983), the adult simple eyes or ocelli (Stark et al 1984;Moses et al 1989;Stark and Sapp 1989), and the larval photoreceptor or Bolwig's organ (Moses et al 1989). In the retina, we demonstrated that only the photoreceptor cells have a cell-autonomous requirement for glass function (Moses et al 1989).…”
mentioning
confidence: 58%
“…Since the TRP protein is expressed in both compound eye and ocellus, it does not appear that TRPprotein is specific to any particular opsin isoform. Ultrastructurally, however, there are several features found in common between the compound eye and the ocellus that are not apparent in the larval photoreceptor (Pollock and Benzer, 1988;Stark et al, 1989). In particular, the structure and organization of the rhabdomeric microvilli and the subrhabdomeric cysternae is quite similar between the two adult visual organs where true rod-like rhabdomeres are formed.…”
Section: Mab83f6 Identi$ed the Trp Proteinmentioning
confidence: 97%
“…The Drosophila visual system consists of two compound eyes and three ocelli, which are simple eyes located on the adult vertex (Stark et al, 1989). Both types of optical organs develop from a small number of cells that are set aside during development in the early embryo.…”
Section: Introductionmentioning
confidence: 99%